2008
DOI: 10.1111/j.1471-4159.2008.05235.x
|View full text |Cite
|
Sign up to set email alerts
|

Host‐cell specific effects of the nicotinic acetylcholine receptor chaperone RIC‐3 revealed by a comparison of human and Drosophila RIC‐3 homologues

Abstract: RIC‐3 is a transmembrane protein which enhances maturation (folding and assembly) of neuronal nicotinic acetylcholine receptors (nAChRs). In this study, we report the cloning and characterisation of 11 alternatively spliced isoforms of Drosophila melanogaster RIC‐3 (DmRIC‐3). Heterologous expression studies of alternatively spliced DmRIC‐3 isoforms demonstrate that nAChR chaperone activity does not require a predicted coiled‐coil domain which is located entirely within exon 7. In contrast, isoforms containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
93
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(98 citation statements)
references
References 34 publications
(154 reference statements)
5
93
0
Order By: Relevance
“…Since different cell lines may or may not express these accessory proteins, it is likely that the use of different cell lines has yielded different results regarding nAChR α9α10 functional expression. RT-PCR studies have provided evidence of a correlation between the endogenous expression of RIC-3 transcripts and the ability of cells to express functional α7 nAChRs (either endogenously or from heterologous expression of nAChRα7 cDNA) (Lansdell et al, 2008;Lansdell et al, 2005;Williams et al, 2005). For example, although tsA201 cells contain no RIC-3 mRNA, GH4C1 cells show detectable levels of endogenous RIC-3 mRNA as determined by RT-PCR (Lansdell et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Since different cell lines may or may not express these accessory proteins, it is likely that the use of different cell lines has yielded different results regarding nAChR α9α10 functional expression. RT-PCR studies have provided evidence of a correlation between the endogenous expression of RIC-3 transcripts and the ability of cells to express functional α7 nAChRs (either endogenously or from heterologous expression of nAChRα7 cDNA) (Lansdell et al, 2008;Lansdell et al, 2005;Williams et al, 2005). For example, although tsA201 cells contain no RIC-3 mRNA, GH4C1 cells show detectable levels of endogenous RIC-3 mRNA as determined by RT-PCR (Lansdell et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of cell-surface α7 AChRs in this new cell line increased from less than 1% to 20% (Figure 1). On the basis of previous reports [13,14,16,17] , we can surmise that Ric-3 facilitates the correct folding and assembly of α7 subunits at the ER. When the parental SHE-P1-hα7 cells were labeled with fluorescent αBTX, a punctate distribution reminiscent of the ER staining was observed throughout the cell ( Figure 1B).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that AChR folding, assembly and trafficking are influenced by several chaperone proteins. Recent studies have shown that co-expression of α7 AChR and the chaperone RIC-3 facilitates the formation of functional homomeric AChRs in otherwise non-permissive cell types [13,14,16,17] . RIC-3 was originally identified in the nematode Caenorhabditis elegans as a protein encoded by the gene ric-3 (resistance to inhibitors of cholinesterase) and has subsequently been cloned and characterized for mammalian and insect species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shift to a lower temperature is necessary to allow appropriate folding of Torpedo nAChR subunit proteins prior to receptor assembly [115], presumably a consequence of nAChRs from species such as Torpedo being adapted to fold efficiently at temperatures lower than 37°C. Similarly, insect nAChR subunits, when expressed in mammalian cell lines, also require incubation at a temperature lower than 37°C for efficient subunit folding and assembly [96,116,117]. To an extent, these problems with insect nAChRs can be avoided by expression in insect cell lines [62,96,116,118], which are typically maintained at 20-25°C (although difficulties remain with the expression of 10 some invertebrate nAChRs, as will be discussed in more detail below).…”
mentioning
confidence: 99%